Strategi Optimalisasi Produk Kerupuk Santoso untuk Meningkatkan Potensi Ekonomi UMKM di Kelurahan Karangkembang - Muhammad Dzikri Abadi; Vicky Indarto Setyono; Nur Aini; Lusiana Winda H.K; Nurul Hidayatus S (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
This community service project aimed to support the development of the "Kerupuk Santoso" MSME in Karangkembang Village, Lamongan Regency, East Java, through training in business management and digital marketing. While this MSME has significant growth potential, it faces various challenges, including limitations in marketing and management. Through a series of training sessions and mentoring, the MSME operators successfully improved their skills in management and digital technology utilization to expand their market reach. The results of this project show a significant increase in operational efficiency and product competitiveness in a broader market. The support from the local community and the active involvement of KKN students played a crucial role in the success of this program. This initiative is expected to have a long-term positive impact on the local economy and the well-being of the community.